Recurrent Thoracic Duplication Cyst with Associated Mediastinal Gas - Hammad Al-Sadoon; Nathan Wiseman; Victor Chernick (Canadian Respiratory Journal)
Mediastinal cysts are not uncommon in the pediatric age group. Presentation varies from an abnormality found on routine chest radiograph to severe respiratory distress and even respiratory failure. Presentation depends on the age of the patient, the location of the lesion, the extent and the size of the mass, and what structures are involved. The case of a six-year-old boy who presented with recurrence of a mediastinal mass associated with gas two years after surgical removal of an infected esophageal duplication cyst is described. No connection between the cyst and the esophagus to explain the presence of gas was documented. This appears to be the first reported case of esophageal duplication cyst associated with mediastinal gas.